2005
DOI: 10.1097/01.ju.0000145758.80937.7d
|View full text |Cite
|
Sign up to set email alerts
|

The Increasing Incidence of Newborn Circumcision: Data From the Nationwide Inpatient Sample

Abstract: There was a significant increase in the rate of newborn circumcision between 1988 and 2000. The increase may be related to increased recognition of the potential medical benefits of circumcision. However, the increase may also result in a higher incidence of surgical complications of circumcision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 15 publications
2
50
0
1
Order By: Relevance
“…246 The weighted rates of circumcision over the 13-year period from 1991 to 2005 were 40.8% for Medicaid clients versus 43.3% for the uninsured and 64.4% for insured newborns. 5 The associations with insurance status were independent of race/ethnicity and socioeconomic status in this study. 246 As noted, a recent cost-effectiveness analysis by the CDC concluded that newborn circumcision is a societal cost-saving HIV prevention intervention.…”
Section: Financing Newborn Male Circumcisionmentioning
confidence: 64%
See 2 more Smart Citations
“…246 The weighted rates of circumcision over the 13-year period from 1991 to 2005 were 40.8% for Medicaid clients versus 43.3% for the uninsured and 64.4% for insured newborns. 5 The associations with insurance status were independent of race/ethnicity and socioeconomic status in this study. 246 As noted, a recent cost-effectiveness analysis by the CDC concluded that newborn circumcision is a societal cost-saving HIV prevention intervention.…”
Section: Financing Newborn Male Circumcisionmentioning
confidence: 64%
“…4 The NIS indicates that circumcision was performed in 57% of male newborn hospitalizations between 1998 and 2005. NIS data from 1988 to 2008 indicate that the rate of circumcision performed during newborn male delivery hospitalizations increased significantly from 48% in 1988-1991, to 61% in 1997-2000, 5 then declined from 61% to 56% in 2000-2008 6 (Fig 1). Circumcision rates were highest in the Midwestern states (74%), followed by the Northeastern (67%) and Southern states (61%).…”
Section: Nismentioning
confidence: 99%
See 1 more Smart Citation
“…19 Yet, there appears to have been little decline in prevalence of neonatal circumcision in the USA as a result. An estimated 61% of male newborns were recorded as being circumcised on hospital discharge sheets in 2000, 20 and community surveys that include newborns circumcised for religious and other reasons outside the hospital setting have found higher neonatal male circumcision prevalence of 76-92%. 21 On the other hand, declines were seen both in Canada and Australia following similar statements by the medical authorities in those countries, and in the United Kingdom following the decision not to cover neonatal male circumcision on the National Health Service.…”
Section: Epidemiology and Acceptability Of Male Circumcisionmentioning
confidence: 99%
“…Moreover, the newborn rate is increasing by 6.8% per year in the US. 85 In the UK, a rate of 6% is suggested. However, publications give: 7-10% for boys aged <15 years, 86 12.5% for ages 16-24 years, 15.9% for ages 25-34 and 26.4% for ages 35-44 (n = 1,874, 2,111 and 2,049, respectively), 87 and 48% in 305 London males aged 4-93 (av.…”
Section: Ratesmentioning
confidence: 99%